Strategi Guru Pendidikan Al-Qur’an dalam Mengatasi Kesulitan Membaca Al-Qur’an pada Madrasah Aliyah Pondok Pesantren Nahdlatul Ulum Soreang Kabupaten Maros - A. Nurul Firdayanti.S; Ahmad Hakim; Salim Hasan (Journal on Education, 2023)
The results showed that the Al-Qur'an education teacher's strategy in overcoming difficulties in reading the Qur'an at Madrasah Aliyah Pondok Pesantren Nahdlatul Ulum Soreang Maros, as follows; 1) Identifying the difficulties of reading the Qur'an experienced by students, 2) Registering students who are proficient and not proficient yet in reading the Qur'an, and 3) Implementing learning methods. The learning process engages opening the lesson, presenting the material with the guidelines of the Qur'an and the guideline book of Tajweed “matan tuhfatul athfal wal ghilman”, and closing the lesson by evaluating students, providing additional assignments, and giving motivation. The supporting factors for teachers in overcoming the learning difficulties of Al-Quran faced by the students of Madrasah Aliyah (MA) Pondok Pesantren Nahdatul Ulum Soreang Maros, namely; 1) Availability of facilities and infrastructure, and 2) Policy support from the Madrasah. There are several inhibiting factors of the Al-Qur'an teacher in overcoming the student’s difficulties in reading the Al-Qur'an at Madrasah Aliyah Boarding School of Nahdlatul Ulum Soreang Maros involved several related components, as follows; 1) Lack of basic abilities possessed by the students, 2) Lack of motivation to learn owned by the students, and 3) Lack of learning time in the class.